Association of platelet count with mortality in patients with infectious diseases in intensive care unit: a multicenter retrospective cohort study. (17th November 2022) - Li, Jiamei; Li, Ruohan; Jin, Xuting; Ren, Jiajia; Du, Linyun; Zhang, Jingjing; Gao, Ya; Liu, Xiu; Hou, Yanli; Zhang, Lei; Song, Zhenju; Song, Jingchun; et al.
Abstract: Platelets play important roles in thrombosis, hemostasis, inflammation, and infection. We aimed to evaluate the association between platelet count and its variation trend and prognosis of patient with infectious diseases in intensive care units (ICUs). This retrospective cohort study extracted 4, 251 critically ill adult patients with infectious diseases from the eICU Collaborative Research Database, whose platelet counts were measured daily during the first 7 days after admission. In the survivors, platelet counts decreased in the first days after admission, reached a nadir on day 3, and then returned and continued to rise above the admission value. In non-survivors, the platelet counts decreased after admission, without a subsequent upturn. We defined three subgroups according to the nadir platelet counts within 7 days: ≤50, 50–130, and ≥130 × 10 9 /L, corresponding to high, intermediate, and low ICU mortality. A decreased platelet count was associated with increased ICU mortality (intermediate vs. low: 1.676 [1.285–2.187]; high vs. low: 3.632 [2.611–5.052]). In conclusion, during the first 7 days, platelet counts decreased after ICU admission, while increased subsequently in the survivors but not in the non-survivors. ICU mortality risk increased as nadir platelet count decreased below 130 × 10 9 /L, and further boosted when it reached below 50 × 10 9 /L.